An investigation on the environmental knowledge and attitudes of senior middle school students in the Democratic People's Republic of Korea. Issue 2 (2nd April 2020) - Choe, Jin-Hyok; Kim, Chol-Hyok; Ri, Gwang-Ho
Abstract: The purpose of this study is (1) to assess the level of environmental knowledge and attitudes of students in grade 1 to 3 of senior middle schools in Pyongyang, Democratic People's Republic of Korea, (2) to estimate whether the grade level and gender influence their environmental knowledge and attitudes or not, and (3) to research the relationship between environmental knowledge and attitudes. Participants were 423 students ranging from the first to third grade of 10 different senior middle schools. They were administered a questionnaire to assess their environmental knowledge and attitudes. Results show that participants had inadequate environmental knowledge but their attitudes were relatively favourable. The environmental knowledge level of grade 3 students was significantly higher than the grade 1 and 2 students and the level of grade 1 students was slightly higher than that of grade 2 students. This holds true for their environmental attitudes. Boys demonstrated higher environmental knowledge and more positive environmental attitudes as compared to girls. We found the significant correlation between students' environmental knowledge and attitudes but it was moderate ( r = .302, p < .01).